The food web perspective on aquatic biofilms. Issue 4 (25th June 2018) - Weitere, Markus; Erken, Martina; Majdi, Nabil; Arndt, Hartmut; Norf, Helge; Reinshagen, Michael; Traunspurger, Walter; Walterscheid, Anja; Wey, Jennifer K.
Abstract: Biofilms, the complex communities of microbiota that live in association with aquatic interfaces, are considered to be hotspots of microbial life in many aquatic ecosystems. Although the importance of attached algae and bacteria is widely recognized, the role of the highly abundant biofilm‐dwelling micrograzers (i.e., heterotrophic protists and small metazoans) is poorly understood. Studies often highlight the resistance of bacterial biofilms to grazing within the microbial food web and therefore argue that the micrograzers have a modulating role (i.e., have effects on biofilm phenotype) rather than a direct trophic role within biofilms. In the present review, we show that this view comes too short, and we establish a conceptual framework of biofilm food webs consisting of three major elements. (1) Energy pathways and subsidization from plankton. As inhabitants of interfaces, biofilm‐dwelling grazers potentially access both planktonic organisms and surface‐associated organisms. They can play an important role in importing planktonic production into the biofilm food web and thus in the coupling of the planktonic and benthic food webs. Nevertheless, specialized grazers are also able to utilize significant amounts of autochthonous biofilm production. (2) Horizontal complexity of the basal food web. While bacteria and algae within biofilms are edible in general, food quality and accessibility of both bacteria and algae can differ considerably between different prey phenotypes occurring during biofilm formation with respect to morphology, chemical defense, and nutrient stoichiometry. Instead of considering bacteria and algae within biofilms to be generally resistant to feeding by micrograzers, we suggest considering a horizontal food‐quality axis to be at the base of biofilm food webs. This food quality gradient is probably associated with increasing costs for the micrograzers. (3) Vertical food web complexity and food chain length. In addition to the consumption of bacteria and algae, many predatory micrograzers exist within biofilm food webs. With the help of video microscopy, we were able to demonstrate the existence of a complex food web with several trophic levels within biofilms. Our conceptual framework should assist in integrating food web concepts and processes into whole‐biofilm budgets and in understanding food‐web‐related interactions within biofilms.